PERANCANGAN JARINGAN KOMPUTER SEBAGAI KONSEP UNTUK MEMBANGUN LABORATORIUM MULTIMEDIA DAN BAHASA DENGAN MENGGUNAKAN METODE PENDEKATAN PPDIOO - Fajar Sodiq (Politeknik Negeri Indramayu, 2023)
The construction of a computer laboratory at YPPI Rembang University is needed to meet the needs of new study programs. With the existence of a computer laboratory, it is hoped that it can support the lectures carried out for the Information Systems Study Program in particular. The construction of the laboratory requires a concept or planning based on the area of ​​the location, as well as hardware specifications that will be used to design a computer network. The design of this computer network is used as a reference or description when it will be implemented which devices will be used to build the multimedia and language laboratory. This study uses the PPDIOO approach where the method has stages in the form of operators and also optimization of hardware performance as well as computer network devices used so that it is expected to facilitate maintenance in hardware, software and computer network devices, so as to minimize damage or errors in the communication process between client PCs and campus server PCs as well as control PCs in multimedia and language laboratories.